The behaviour of cobalt during nickel smelting and converting - Grimsey, Eric (AusIMM, 1992)
This paper outlines the thermodynamic and mass balance principles which affect the distribution of cobalt between matte and slag during the pyrometallurgical treatment of nickel - copper sulfides and considers the implications with regard to maximising the recovery of cobalt from the smelting and converting circuit.